Dept. of oral medicine and Radiology JSS Dental College and Hospital, JSS Academy of Higher Education and Research, SS Nagar, Mysuru Karnataka - 570015, (Journal of Forensic Medicine & Toxicology, 2020)
Trauma is one of the leading preventable causes of death in developing countries, and is a major health and social problem. Since prehistoric times, head and the chest has been looked upon as one of the most vulnerable regions of the body and injuries involving it have always been considered very serious1. The study was conducted on dead bodies with history of accidental death brought for medicolegal postmortem examination to the department of forensic medicine of Government Medical College, Nagpur. The present study concluded that Male prdominated with male to female ratio 5.5:1.Highest incidents of death due to accident were found in the age group 31 to 40 years. Maximum deaths occurred within one hour of accidental deaths. Maximum male casualties were reported in the age group of 21 to 30 years and female casualties more in the age group of 31 to 40 years. .Head injury was the leading cause of accidental deaths.
Keywords: Road traffic accident; head injury; motor cycle; abrasion